Trombocitopenia versus SOFA parapredecir mortalidad en pacientescon sepsis en la Unidad de CuidadosIntensivos de un hospital de tercer nivelde Guatemala - Escobar Jimenez, Nancy; Facultad de Ciencias Medica, Universidad de San Carlos de Guatemala (Universidad de San Carlos de Guatemala, 2019)
e most common coagulation disorder in the intensive care unit isthrombocytopenia. Considering the fundamental role of platelets in hemostasis andas markers of disseminated intravascular coagulation, a significant decrease in plateletcounts is alarming in the context of septic patients, and it is known to be a predictor ofdeath. The objective was to compare the ability of the platelet count with the SequentialOrgan Failure Assessment (SOFA) to predict death in patients with severe sepsis or septic shock. A longitudinal study was conducted with a sample of 29 consecutivecases evaluated during January to December 2015 in the Intensive Care Unit of theGeneral Hospital of Diseases (HGE) of the Guatemalan Social Security Institute.Platelet and SOFA counts were performed at the first and the fih day of hospitalization,documenting the outcome of the patients. 51.7% of the patients were men and 48.3%were women, with an average age of 62.0 (16.9) years, median SOFA on admission of10 units (Q1=4, Q3=14) and platelet median on admission of 196000 (Q1=100000,Q3=250000). e univariate association between thrombocytopenia and death wassignificant (p = .021, RR = 2.45, CI 95% [1.21, 4.99]). According to a Bootstrap test,there is no significant difference between the predictive capacity of SOFA and plateletcount (p = .965). It was concluded that the presence of thrombocytopenia is a simplepredictor of death in patients with severe sepsis or septic shock, with similar capacity to SOFA.